Uniaxial Tensile Stress-Strain Response on the 3D Angle Interlock Woven Fabric Composite - M.Z. Nasrun, F.; F. Yahya, M.; R. Ahmad, M.; A. Ghani, S. (International Journal of Engineering and Technology, 2019)
An experimental study have been performed to investigate the uniaxial tensile stress-strain response on the 3D angle interlock (3DAI) woven fabric composite. The tensile analysis were examined based on different woven fabric set-up parameter of draw-in plan ; pointed (DRW 1), broken (DRW 2), broken mirror (DRW 3), and straight (DRW 4). Meanwhile, the woven fabric composite were produced based on 22 and 25 pick.cm-1 of weft densities. The outcomes produced shown that woven composite sample with 25 pick.cm-1 on DRW 4 projected the highest stress response, 113 MPa. Extensive review indicated that DRW 1 and 4 gave better tensile stress-strain response than the other counterpart.